DIVERSIFIKACIJA RURALNE EKONOMIJE U FUNKCIJI REGIONALNOG RAZVOJA REPUBLIKE SRBIJE - Ćurčić, Nevena; Mirković Svitlica, Andrijana (International Journal of Economic Practice and Policy, 2022)
Pronounced regional disparities represent one of the main features of regional development in Serbia. The regions are economically very uneven, and there are often differences within the regions themselves. The most prominent intra-regional disparity is between urban and rural areas. Rural areas are particularly vulnerable because they have experienced depopulation and economic decline for decades. This problem has been recognized and addressed in the Strategy of Agriculture and Rural Development of the Republic of Serbia from 2014-2024. One of the priority areas of implementation of the operational objectives relates to the diversification of the rural economy and the preservation of cultural and natural heritage. Due to its positive effects on GDP, employment, the balance of payments, investment and population standard, tourism is increasingly becoming an essential instrument for stimulating development, especially in those regions where employment creation through other forms of investment is challenging. Accordingly, this paper aims to present the potential of rural tourism as an endogenous factor of regional and local development through the presentation and analysis of socio-economic indicators and realized tourist traffic in the statistical regions in Serbia. Results of correlation analysis indicate a positive correlation between the number of tourists and number of employees, number of employees per 1000 inhabitants and average net earnings in NUTS 3 regions in Serbia.
Keywords: rural economy; diversification of business; tourism; regional development; disproportion; Republic of Serbia